f(x)=x to the 2nd power

f(x)=7(x+2)to the 2nd power

f(x)=-x to the 3rd power

Please let me know if you need any clarification. I'm always happy to answer your questions.

A. f(x)=x to the second power implies that the derived value of x must be raised to power 2 or squared

Hence for the first function, we substitute x with -4 and power the result by 2

The answer is -4squared hence g(x) =16

B.For the second function, we substitute x in the expression and square the result too= 7(-4 squared)+2)

Use bodmas.....g(x).=7(16+2)=126

C. for f(x)=-x we establish that g(x)=-(-4 power three/cubed)

g(x)=-(-64)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up